A Whole Mind, an Unconquered Eye: Self-Reliance and Freedom in Henry James’s Daisy Miller - Martínez Serrano, Leonor María (Complutense Journal of English Studies, 2023)
Looking at Henry James’s literary contexts can fruitfully help shed light on his work. Brilliantly versed in the literary traditions of his time, he was influenced by American, English, French and Russian writers. This article traces the influence of Emerson’s notions of freedom, natural spontaneity, innocence and self-confidence as expressed in his essays “Nature” (1836) and “Self-Reliance” (1841) in Daisy Miller (1878), whilst it investigates the ways James’s novella articulates the all-important dichotomy of self-sufficiency (individual freedom, autonomy, innocence) vs. social conformity (fear, heteronomy, hypocrisy) at play in the narrative. Daisy is the female embodiment of self-reliance as conceptualised in Emerson’s homonymous essay – a free, innocent, uncultivated, wild, and unsophisticated spirit – and so she is never afraid. Epistemology turns out to be central to the conception of the novella, as Winterbourne and the American matriarchs are shown struggling to grasp the protagonist’s puzzling innocence and true nature. As Daisy is a wild being living in accord with Nature as conceived by Emerson, the novella is punctuated by critical moments where the heroine is most at home when enmeshed in the green world, particularly in the outdoor scenes in the Château de Chillon in the Swiss Alps, the Palaces of the Caesars, the Colosseum and the Protestant cemetery in Rome.